Subdural haematoma associated with an arachnoid cyst after repetitive minor heading injury in ball games. Issue 4 (23rd July 2004) - Demetriades, A K; McEvoy, A W; Kitchen, N D
Abstract : We report the case of a chronic subdural haematoma caused by repetitive heading of a football which led to the diagnosis of a middle fossa arachnoid cyst. The association between arachnoid cysts and subdural haematoma is discussed as are safety implications in sporting injuries.